Efektivitas Pemberian Makanan Tambahan (PMT) terhadap Kenaikan Tinggi Badan dan Berat Badan Balita Stunting di Puskesmas Gunung Kaler Tangerang - Nur Laelah; Sukarni Setya Ningsih (Universitas Malahayati Lampung, 2024)
ABSTRACT WHO in 2020 stated that the prevalence of stunting under five worldwide was 22 percent or as many as 149.2 million. The prevalence of stunting in Indonesia (24.4%) is better than Myanmar (35%), but still higher than Vietnam (23%), Malaysia (17%), Thailand (16%) and Singapore (4%). The prevalence of stunting in West Java in 2021 is 24.5%, while in Bekasi Regency it is 21.3%. The impact of stunting is intelligence, impaired physical growth, high risk of diabetes, obesity, cancer, stroke, and low economic productivity. Knowing the effectiveness of giving supplementary food to the increase in height and weight of stunting toddlers. Quasi experimental with one group pretest-posttest design. The sample in this study were all toddlers who were stunted at the Gunung Kaler Health Center as many as 30 people. The sampling technique used the total sampling technique. The average height of stunted toddlers before being given PMT biscuits was 75.59 kg and after that it was 83.36 kg. The average body weight of stunted toddlers before being given PMT biscuits was 8.88 kg and after that it was 13.30 kg. Supplementary feeding (PMT) is effective in increasing the height and weight of stunted toddlers with a p value of 0.000. Provision of additional food is effective in increasing the height and weight of stunting toddlers. It is hoped that health workers will provide counseling more often about the importance of providing balanced nutrition to toddlers to avoid stunting Keywords: Provision of Supplementary Food, Stunting ABSTRAK WHO tahun 2020 menyebutkan bahwa prevalensi balita kerdil (stunting) di seluruh dunia sebesar 22 persen atau sebanyak 149,2 juta. Prevalensi stunting di Indonesia (24,4%) lebih baik dibandingkan Myanmar (35%), tetapi masih lebih tinggi dari Vietnam (23%), Malaysia (17%), Thailand (16%) dan Singapura (4%). Prevalensi stunting di Jawa Barat tahun 2021 sebesar 24,5%, sedangkan di Kabupaten Bekasi sebesar 21,3%. Dampak dari stunting adalah kecerdasan, gangguan pertumbuhan fisik, risiko tinggi diabetes, kegemukan, kanker, stroke, dan rendahnya produktivitas ekonomi. Mengetahui efektivitas pemberian makanan tambahan terhadap kenaikan tinggi badan dan berat badan balita stunting. Quasi eksperimental dengan rancangan one group pretest-posttest design. Sampel dalam penelitian ini adalah seluruh balita yang mengalami stunting di Puskesmas Gunung Kaler sebanyak 30 orang. Teknik pengambilan sampel menggunakan teknik total sampling. Rata-rata tinggi badan pada balita stunting sebelum diberikan biskuit PMT sebesar 75,59 kg dan sesudahnya sebesar 83,36 kg. Rata-rata berat badan pada balita stunting sebelum diberikan biskuit PMT sebesar 8,88 kg dan sesudahnya sebesar 13,30 kg. Pemberian makanan tambahan (PMT) efektif terhadap kenaikan tinggi badan dan berat badan balita stunting dengan nilai p value 0,000. Pemberian makanan tambahan efektif terhadap kenaikan tinggi badan dan berat badan balita stunting. Diharapkan tenaga kesehatan lebih sering lagi memberikan penyuluhan tentang pentingnya pemberian gizi seimbang pada balita supaya terhindar dari stunting Kata Kunci : Pemberian Makanan Tambahan, Stunting